The Effect of an Extract and Fractions of Date Pits on Some Plasma Constituents, Reproductive Hormones, and Testicular Histology in Male Mice. (25th October 2022) - Al Za'abi, Mohammed; Ali, Badreldin H.; Ali, Haytham; Manoj, Priyadarsini; Ashique, Mohammed; Nemmar, Abderrahim; Cahlíková, Lucie
Abstract : Pits of dates ( Phoenix dactylifera L.) have numerous nutritional benefits that could have wide-ranging applications. This study aimed to examine the effects of administering three extracts from powdered date pits on some basic physiological parameters, plasma constituents, reproductive hormones, and testicular histology in CD1 male mice. Three groups received doses of 100 mg/kg/day of lyophilized extract, a nonpolar fraction, and a polar fraction of date pits by oral gavage for 28 consecutive days. For the control, one group was administered a 1 mL/kg concentration of distilled water. The three different extracts significantly increased the plasma testosterone level but showed no significant effect on estradiol or luteinizing hormone levels, except for estradiol reduction in the polar extract group. The measured physiological or biochemical parameters or testicular histology also demonstrated no significant differences between the control mice and those mice treated with the three extracts, except for reductions in plasma urea in all extracts and in total protein in the nonpolar extract. Therefore, date pit extracts may potentially be used as a safe and effective dietary supplement. However, further investigation is needed.